Metabolic Dysfunction-Associated Steatotic Liver Disease Complicated by Diabetes: Pathophysiology and Emerging Therapies - Hisanori Goto; Toshinari Takamura (Journal of Obesity & Metabolic Syndrome)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is a liver manifestation of diabetes that is often associated with obesity and insulin resistance, with hyperglycemia worsening its progression. Recent studies have shown a bidirectional relationship between MASLD and diabetes: MASLD contributes to insulin resistance, and hyperglycemia accelerates the progression of MASLD to metabolic dysfunction-associated steatohepatitis (MASH). Hepatokines upregulated by overnutrition and hyperglycemia are implicated in the link between liver steatosis and insulin resistance in skeletal muscle, highlighting inter-organ crosstalk in the progression of both MASLD and diabetes. In individuals with diabetes, hyperglycemia and free fatty acid influx promote de novo lipogenesis and enhance lipid oxidation and oxidative phosphorylation in the liver, potentially leading to increased oxidative stress, inflammation, and fibrosis. Transcriptome analyses of human MASH and diabetic MASH model animals have revealed liver endothelial cell damage in diabetic conditions. Most drugs proven effective for MASH in randomized controlled trials are antidiabetic agents. Recently, pioglitazone, glucagon-like peptide-1 (GLP-1) receptor agonists, and dual agonists of glucose-dependent insulinotropic polypeptide and GLP-1 have been recommended as preferred options for glycemic control in MASH patients with type 2 diabetes mellitus. Meanwhile, the efficacy of sodium-glucose cotransporter 2 inhibitors for MASH has also been reported, primarily in East Asia. Given the diversity in MASLD/MASH pathology among populations, ranging from lean to obese individuals with and without diabetes, population-specific approaches might help elucidate the pathogenesis of MASLD/MASH and develop treatment strategies.